Against Ptolemy? : Cosmography in Early Kalām omar anchassi - Anchassi, Omar (JAOS, 2022)
This article explores how mutakallimūn engaged with competing visions of the cosmos—traditionalist and Aristotelian-Ptolemaic—to the beginning of the sixth/ twelfth century. Drawing on works of kalām, Quran commentary, and items from other genres, I demonstrate that rationalist theologians remained divided on such questions as the shape of the earth to the end of this period. These disagreements, moreover, cannot be explained in terms of school affiliation. Based on a comprehensive examination of published sources, I argue that cosmographical opinion among mutakallimūn was a function of exposure to late ancient learning, intellectual formation, and personal inclination more than doctrinal commitment.